Ecology - Rolston, Holmes, 1932-2025, author; Macmillan Reference USA, publisher (Colorado State University. Libraries, 2015)
Ecology is the logic of living creatures in their homes. Ecology mixes with ethics, an ecological (or environmental) ethics urging that humans ought to find a lifestyle more harmonious with nature. Humans have always had to rest their cultures on a natural life support system. Environmental engineers may now claim that the principal novelty of the new millennium is that Earth will be a managed planet in an Anthropocene epoch. Such claims bring increasing concern how far nature can and ought to be transformed into humanized nature. Thinking of humans as fitting themselves into a sustainable biosphere is a better logic of being at home on Earth.
Article also appeared in previous edition: Encyclopedia of science, technology, and ethics (Detroit, MI: Macmillan Reference USA, ©2005).
Keywords: environmental science; ecology; Anthropocene epoch; ecosystems; environmental ethics; conservation